Against a Wen: An Anglo-Saxon Charm: An Anglo-Saxon Charm - Corbett, Maryann (Ars Medica, 2022)
This anonymous metrical spell, inserted in a twelfth-century hand in the tenth-century British Library MS Royal 4A xiv, testifies that trust in pagan medical magic coexisted for a long time with Christian faith in early England.